Viral Infections Boost Prokaryotic Biomass Production and Organic C Cycling in Hadal Trench Sediments - Manea, Elisabetta; Dell’Anno, Antonio; Rastelli, Eugenio; Tangherlini, Michael; Nunoura, Takuro; Nomaki, Hidetaka; Danovaro, Roberto; Corinaldesi, Cinzia (Frontiers in Microbiology, 2019)
Hadal trenches are among the most remote and least explored ecosystems on Earth and can support high benthic microbial standing stocks and activities. However, information on the role of viruses in such ecosystems and their interactions with prokaryotic hosts is very limited. Here, we investigated activities of benthic viruses and prokaryotes and their interactions in three hadal trenches (Japan, Izu-Ogasawara and Mariana trenches) and in their nearby abyssal sites. Our findings reveal that these hadal trenches, compared with the surrounding abyssal sites, support higher abundances and biomasses of prokaryotes. In addition, the high prokaryotic biomasses of hadal trenches could favor high rates of viral infection and cell lysis, especially in the Japan Trench. Hadal viruses can release large amounts of highly labile and promptly available organic material by inducing cell lysis, which could contribute to sustain benthic prokaryotes and decrease their dependency on the enzymatic digestion of the more refractory fraction of sediment organic matter. Our results suggest that this process can contribute to explain the discrepancy between high prokaryote biomass and apparent low efficiency in the utilization of the sedimentary organic matter in the hadal ecosystems. Concluding, hadal trenches may be characterized by a highly dynamic viral component, which can boost prokaryotic biomass production, thereby profoundly influencing the functioning of these remote and extreme ecosystems.